NUTRITIONAL CHALLENGES AND ENERGY AVAILABILITY IN SCHOOL-AGED FEMALE GYMNASTS: IMPLICATIONS FOR HEALTH AND PERFORMANCE - Fang Jinlin, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: School-aged female gymnasts are particularly vulnerable to inadequate energy intake due to sport-specific aesthetic demands and high training loads. This narrative review examines the current evidence on energy availability and macronutrient distribution and their effects on growth, body composition, hormonal balance, and athletic performance in young female gymnasts. Low energy availability (LEA) has been consistently associated with delayed maturation, menstrual dysfunction, reduced bone mineral density, and increased injury risk. In addition, imbalanced macronutrient intake—especially insufficient carbohydrate and fat consumption—can further impair metabolic and endocrine function. Practical nutritional strategies, including adequate caloric intake, balanced macronutrient distribution, and individualized dietary planning, are essential for optimizing both health and performance outcomes. Future studies should focus on longitudinal and intervention-based designs in youth athletic populations.